Penggunaan Multimedia Interaktif Praktikum Titrasi Asam Basa Dalam Meningkatkan Pemahaman Titrasi Asam Basa Mahasiswa Institut Studi Islam Sunan Doe - Wutsqo, Urwatil (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This study discusses the problem of using interactive multimedia practicum acid-base titration in improving understanding of acid-base titration. The purpose of this study was to determine the process of developing interactive multimedia products for acid-base titration practicum, determine the feasibility of interactive multimedia products for acid-base titration practicum as learning media, study the effect of using interactive multimedia for acid-base titration practicum on understanding acid-base titration, and study the effect of using interactive multimedia for acid-base titration practicum on acid-base titration practicum experience. This research uses the 4-D development model for the process of developing multimedia practicum of acid-base titration, and uses a quasi-experimental research design (Quasy Experimental Design). This research was conducted at the Sunan Doe Institute of Islamic Studies on science students, namely the study programmes of tadris chemistry and tadris science. The results of this study will be discussed further.